Current trends in surgical treatment for infertility associated with polycystic ovary syndrome - I.I. Grishin; T.G. Chirvon; O.R. Oguede (РМЖ. Мать и дитя, 2022)
I.I. Grishin, T.G. Chirvon, O.R. Oguede Pirogov Russian National Research Medical University, Moscow, Russian Federation Polycystic ovary syndrome (PCOS) is a common endocrine disorder and one of the main causes of anovulation in women of childbearing age. Surgical procedures for infertility treatment in women with PCOS have been used in clinical practice for a long time. As a rule, they are considered as a second-line therapy after the first-line pharmacological treatment. Since recently the focus has shifted to the comparison of different types of surgical treatment techniques, their effects on the ovarian function, and the development of adhesions. The article reviews the most common surgical options for PCOS treatment in various patient groups and the key results obtained in the top importance studies undertaken in this area. Surgical treatment of PCOS in properly selected patients seems to be a cost-effective therapeutic option that has comparable success rates to ovulation induction with gonadotropins. Laparoscopic ovarian drilling is one of the preferable minimally invasive techn iques. This procedure is recommended for patients who have other indications for laparoscopy, or if there is a high risk of ovarian hyperstimulation syndrome and multiple pregnancy, or if there are contraindications to multiple pregnancy. At the same time, it is emphasized that the uniform regimens and standards of PCOS surgical treatment have not been optimized so far. Their outcomes are understudied and the issue is still open for discussion. Keywords: laparoscopic ovarian drilling, polycystic ovary syndrome, ovarian hyperstimulation syndrome, anovulation, infertility, adhesions. For citation: Grishin I.I., Chirvon T.G., Oguede O.R. Current trends in surgical treatment for infertility associated with polycystic ovary syndrome. Russian Journal of Woman and Child Health. 2022;5(3):209–214 (in Russ.). DOI: 10.32364/2618-8430-2022-5-3-209-214.